1963
DOI: 10.1139/b63-068
|View full text |Cite
|
Sign up to set email alerts
|

The Bioelectric Potentials of Plants and Their Functional Significance: V. Some Daily and Seasonal Changes in the Electrical Potential and Resistance of Living Trees

Abstract: Continuous records of bioelectric stem potentials have been made throughout a season for three kinds of tree: Ulmus americana L., Pinus resinosa Ait., and Acer saccharum Marsh. Daily measurements of potential and resistance for a 15-month period have also been made on a maple and some direct measurements of current are also given. A yearly rhythm was clearly visible, also daily cycles, and during the growing season cycles of 5-minute frequency. The yearly and daily rhythms have been interpreted in terms of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1969
1969
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…This may explain Fensom's findings that the potential difference fell rapidly at the onset of rainfall. (Fensom 1963a) The fact that exceptionally tall trees such as sequoia sempervirens are only found in fog-prone coastal habitats might seem to be contrary to the current hypothesis but it seems possible that explanation of foliar absorption during foggy periods may be paired with electrically-assisted water uptake from the ground in dry and sunny periods to provide the trees with a strategy for either condition.…”
Section: Further Corollaries Of the Possible Influence Of The Earth'smentioning
confidence: 61%
See 1 more Smart Citation
“…This may explain Fensom's findings that the potential difference fell rapidly at the onset of rainfall. (Fensom 1963a) The fact that exceptionally tall trees such as sequoia sempervirens are only found in fog-prone coastal habitats might seem to be contrary to the current hypothesis but it seems possible that explanation of foliar absorption during foggy periods may be paired with electrically-assisted water uptake from the ground in dry and sunny periods to provide the trees with a strategy for either condition.…”
Section: Further Corollaries Of the Possible Influence Of The Earth'smentioning
confidence: 61%
“…(Rosene 1937, p391) In the 1940s, Burr (1945Burr ( , 1947 investigated the electrical potentials in living maple trees and found that, although the potentials were variable, the upper part of the tree was positive with respect to the base from late May through to the end of December. (Burr 1947 , Fig 2 p313 (Fensom 1957(Fensom , 1958(Fensom , 1959(Fensom , 1962(Fensom , 1963a which included continuous measurements of bioelectric stem potentials in three kinds of tree (Ulmus americana L., Pinus resinosa Ait., and Acer saccharum Marsh). Fensom demonstrated a yearly tendency for the upper electrode in the Elm trees to become more positive with respect to ground, and a daily cycle with a definite daily rhythm (Fensom 1963a, p833 Studies by Schuch (1968) and Morat, Le Mouël & Granier (1994), quoted in Gibert et al (2006), also found electrical potential gradients in a spruce tree and a chestnut tree respectively.…”
Section: Previous Electrical Measurements On Living Treesmentioning
confidence: 99%
“…This may be a ground electrode put in the soil (as we do in our experiments) or a reference electrode at some other part of the plant 12 . Measurements using inserted (extracellular) electrodes were, for example, made with various tree species showing daily and yearly rhythms 13 . However, the insertion of electrodes inevitably causes wound reactions.…”
Section: Extracellular Recordingmentioning
confidence: 99%
“…Thermodynamic considerations on the state of water in tree trunks during transport to the tree tops suggest a difference of electrochemical potentials between different tree heights. Potential differences were actually repeatedly measured between tissues of living trees and the soil and daily and seasonal changes of the signal were observed (Fensom 1963, Toriyama 1991, Morat et al 1994, Koppán et al 2000, Gibert et al 2006. For a period of 11 years, Toriyama (1991) studied electrical potentials on Albizia julibrissin trees, observing daily changes in the order of 40 mV.…”
Section: Introductionmentioning
confidence: 99%
“…What he apparently observed was probably the effect of groundwater level changes, which should have an effect on the water supply to trees. The study of Fensom (1963) on an elm tree (Ulmus) yielded typical potential differences between 20 and 40 mV with the highest potential difference observed in the afternoon. He observed a direct correlation between the electrical potentials and the sap flow, and assumed an electrokinetic phenomenon.…”
Section: Introductionmentioning
confidence: 99%